Build wind capacities at windy locations? Assessment of system optimal wind locations - Frank Obermüller (Institute of Energy Economics at the University of Cologne (EWI), 2017)
In recent years, the installed capacities of renewable energies have steadily been increasing. This raises the question for optimal locations of renewables. Ideally, the market prices induce efficient locations. Distorting effects, i.e. non incorporation of the physical grid situations, could lead to sub-optimal regional incentives compared to a system optimal perspective. In this paper, the wind production revenues under nodal and zonal pricing are investigated. The analysis is extended to the widely used wind value factor. The analysis identifies the zonal pricing wind revenues as inefficient location signals. Location signals need to consider the grid situations. Wind revenues could face an average increase of 21% and more than 200% for certain locations. This is highly relevant to design efficient subsidy schemes or to identify regional grid and capacity extension necessities.
Keywords: Q42; Q48; 330; Optimal Wind Locations; Wind Production; Market Revenues; Market Value; Electricity System Model; Nodal Pricing; Zonal Pricing